Literatura em cena: a ficção especulativa e o cinema brasileiro contemporâneo - PEREIRA, Enzo de Sousa (2023)
The relation between literature and cinema is marked by transformations over the history. From the born of cinematographic language to its developments, the speculative fiction marks an importante space in the seventh art. While in the classic cinema the language appreaches the literary genres in a tangible way, the contemporary cinema seem to hybridize its elements, offering alternative perspectives of the unusual, about the literary genres icons. This research has as its objective to analyse the manifestation of the speculative fiction in the contemporary brazilian cinema, using as main clipping the works A Alegria (2010), de Felipe Bragança e Marina Meliande, Terminal Praia Grande (2019), de Mavi Simão, As Boas Maneiras (2018), de Marco Dutra e Juliana Rojas e A Febre (2019), de Maya Da-rin. In the construction of analyses, it applies the concept of flow cinema in its aesthetics, simbolics and visual elements. Dialoguing, therefore, the speculative fiction literature next to the manifestation in the cinematographic language. As the theorical support, it is used the writtings of Alexander Meireles and Fabrício Basílio to discuss the spective fiction and the fantastic as cinematographic genres, as well as the theorists David Roas and Remo Ceserani, in the preparation of intersections between the literary fantastic and the cinematographic speculative fiction. To the methodology, its contextualized central concepts to the research, just as the develpment of literature and speculative fiction over the history. Followed by analyzes done with the comparative methodology, establishing relations between the literary speculative fictions and its aspects in the cinematographic language. From the analyzes, its aponted the results that verify a brazilian production of speculative fiction very diverse, with an autorship character and techinical inovation, where the references of the international literature and cinema are mixed together. A production whose dialogue with the big public its intense, especially throught Other audiovisual products like series, games and tv shows.